O ensino pre-figurativo de Hans-Joachim Koellreutter na visão de cinco de seus ex-alunos - Gilberto Rezende Junqueira (2018)
The german-brazilian musician and professor Hans-Joachim Koellreutter was one of the most important names in the history of Brazilian Music Education in the 20th century. He worked in the major cultural centers of the country and influenced a generation of musicians and musical educators who stood out in their expertise fields. Koellreutter developed a pedagogical approach for the Musical Education which he called Pre-Figurative Teaching. This research aimed to identify categories that characterize Koellreutters Pre-Figurative Teaching as well as the influence of those elements in the pedagogical practices used, later, by teachers or professors who were their students. Qualitative methodological procedures were adopted in this research based mainly on the analysis of texts, documents and other available materials. Furthermore, semi-structured interviews with the five Koellreutters former students, who work in important institutions for music learning in Belo Horizonte, were conducted. Based on the analysis of these interviews, six categories that define Pre-Figurative Teaching were identified: (1) students valorization (2) questioning and reflexive posture; (3) integration and transcendence of values; (4) emphasis on the relationships and on non-linear processes; (5) autonomy, originality and criativity; (6) emphasis on experience and qualitative aspects. The interviewed former students testemonials were articulated with Koellreutters texts and the ones of other authors in order to clarify such categories. It was concluded in this research that even if the influence of Koellreutter's pedagogical performance was restricted to the regions and institutions where he acted, he reverberated in some way in the practice of his former students, many of whom today act as music teachers in important educational centers of the country, demonstrating that the Pre-Figurative Teaching continues being relevant facing the current paradigms in the Brazilian Musical Education of the present time.